PENGARUH PEMAHAMAN PERATURAN, OMSET, PEMERIKSAAN, SANKSI, RELASI SOSIAL, DAN PERSAINGAN USAHA TERHADAP KEPATUHAN WAJIB PAJAK RESTORAN - Ramadhan S.S Manafe; Aaron M. A. Simanjuntak; Hastutie Noor Andrianti (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
The research aims to determine the factors that influence the taxpayer compliance with the restaurant in Jayapura in fulfilling its obligations to deposit the restaurant tax. Factors used among others: Regulatory understanding, turnover, investigations, sanctions, social relations, and business competition. The number of respondents used in this study is 100 mandatory the registered restaurant tax at Jayapura's regional revenue Service. Techniques the analysis used is a double linear regression technique. The results showed that the regulatory understanding factors, of income/turnover, significantly affect the taxpayer's compliance Restaurant. While the sanctions, investigations, social relations, and business competition factors Taxpayer compliance with the restaurant in Jayapura City.